How Work Stress and Work Environment Influence Job Satisfaction, Retention Study at Jakarta Office State-Owned Airlines Employees - Tinjung Desy Nursanti; Mira Aisyah; Noriska Velvia; Silmi Afifah (Jurnal Ilmu Manajemen & Ekonomika, 2020)
Management changes that occurred at PT. XYZ Jakarta office caused several employees to undergo change positions. With the change in position, employees have to adapt again to new responsibilities. Therefore, the purpose of this study was to determine and understand the effect of work stress and work environment on job satisfaction and its impact on employee retention. This research is quantitative descrip-tive research conducted by distributing questionnaires to all divisions in PT. XYZ Jakarta office as many as 129 respondents. The data analysis used is Path Analysis, after all data has been collected for pro-cessing. The results showed that each variable had a significant influence between one variable and anoth-er. The highest value that has the most influence on the employee retention variable is the work environ-ment variable. Suggestions for PT. XYZ Jakarta office is to pay more attention to the working environment conditions in the company .